The ‘Memories’ of Terrorism: The Victims of Political Violence and the Secondary School in the Basque Country (2005-2021) - Mota Zurdo, David (Historia y Memoria de la Educación, 2022)
Beginning in October 2011, Basque and Spanish institutions have immersed themselves in the analysis of the recent past of the Basque Country, emphasizing the history and memory of terrorism. The study of this traumatic episode has been undertaken by entities such as the Memorial Center for the Victims of Terrorism and Gogora: Institute for Memory, Coexistence and Human Rights. The existence of two memorial organizations with divergent narratives has shown that the Basque society remains polarized, and that it continues to (un-)consciously turn the page of terrorism without even having read it. This disparity of narratives is having its effect on Education. This article focuses on the initiatives implemented by the Basque Government to bring the history of terrorism to the curriculum of the Secondary School in the Basque Country, highlighting the educational programs deployed between 2005 and 2021 to try to delegitimize it. The objective is to show the confrontation of narratives, the reason for the discrepancies and the impact that such circumstances have on how this episode in the history of political violence in Spain is to be transmitted and told.